Science of swimming faster - Riewald, Scott A. 1970-; Rodeo, Scott (Champaign, IL Human Kinetics, 2015)
In a sport where victory is often determined by a fraction of a second, one of the most sought-after secrets is how to swim faster. This repository of swimming research explains and applies the latest science that has and continues to set new performance benchmarks in the sport.
Part I. Swimming Mechanics and Technique -- -- Fluid Dynamics, Propulsion, and Drag / Timothy Wei, Russell Mark, and Sean Hutchison -- Freestyle Technique / Ross H. Sanders and Carla B. McCabe -- Backstroke Technique / Russell Mark -- Breaststroke Technique / Russell Mark -- Butterfly Technique / Ross H. Sanders and Carla B. McCabe -- Techniques for Starts and Turns / Andrew Lyttle and Brian Blanksby -- Analyzing Strokes Using Computational Fluid Dynamics / Matt Keys, Andrew Lyttle, Brian Blanksby, Liang Cheng, and Koji Honda -- -- Part II. Physiological Aspects of Training and Competition -- -- Energy Systems and Physiology / J.M. Stager, Jonathon Stickford, and Kirk Grand -- Periodization and Planning / Scott Riewald -- The Impact of Tapering on Performance / Inigo Mujika and Andrew M. Stewart -- Competition Day Strategies / Scott Riewald -- Analyzing Elite Swimming Performances / Jodi Cossor -- Overtraining and Recovery / Randall L. Wilber -- -- Part III. Applied Sport Sciences -- -- Nutrition : Fueling for Performance / Charlene Boudreau -- Performance Enhancers and Doping Control / Jennifer L. Reed and Andrew L. Pipe -- Swimming Psychology : Merging Mind and Body / James Bauman -- Growth and Development / Rebecca Battista -- Sports Medicine : Swimming Injuries and Their Prevention / Courtney Dawson and Scott A. Rodeo -- Sports Medicine : Illnesses and General Health / Margo Mountjoy -- Strength and Conditioning for Performance Enhancement / Scott Riewald -- -- Part IV. Considerations for Special Groups -- -- Adolescent Swimmers / Morgan Anderson and Jordan D. Metzl -- Masters Swimmers / James W. Miller -- Female Swimmers / Jaci L. VanHeest -- Open Water Swimmers / Steve Munatones -- Adaptive Swimmers / Brendan Burkett
Includes bibliographical references (pages 549-577) and index.
Keywords: Swimming -- Training; Swimming -- Physiological aspects; Sports sciences -- Juvenile literature